PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMA NEGERI 1 KERITANG KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - AGUSSAIRI, AGUSSAIRI (STAI Ma'arif Jambi, 2023)
The success or failure of a school depends on the leadership of the principal, the background factors include, among others, the role of leadership that is not good in developing the quality of education such as